Pelatihan Keterampilan Berbicara Bahasa Indonesia bagi Mahasiswa dari Thailand di Universitas Muhammadiyah Palangkaraya: Indonesian Language Course for Speaking Skill for Thai Students in Muhammadiyah University of Palangkaraya - Usop, Dwi Sari; Lastaria, Lastaria; Supriyadi, Arif (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Indonesian speaking skills is essential for foreign students from Thailand who was educated inIndonesia, especially at Muhammadiyah University of Palangkaraya. Through skills for speakingIndonesian properly, Thai students were able to communicate with people residing in the vicinity.Particularly, in understanding the course material and expression.Indonesian language course for speaking skill for Thai students in Muhammadiyah University ofPalangkaraya aims to make the students able to recognize and understand the diversity of Indonesianand serves as a science to improve impaired speech in the Indonesian language, which will also affectthe ability to write Indonesian.Through course, Muhammadiyah University of Palangkaraya students’ who came from Thailandhas been quite able to recite the alphabet and make a simple sentence that can be used incommunications. However, this ability stills needs to be aharpened in order to become proficientcommunicate using Indonesian.